The United States of America War of 1898 against Spain Empire - Muhamada, Sipan S.; MohammedAmeen, Sipal S. (Journal of Duhok University, 2019)
The new world force emerged at the end of nineteenth century and became a part of the conflict between the greatest forces in order to achieve some political and economical profits. The last decades of the nineteenth century were considered as the golden age of the United States of America as its ranked to be one of the greatest states. The first step that the United State of America took to achieve this rank was to content in war against Spain Empire in 1898, and it tried to obtain some political and economical profits from the dying empire. The researchers that were done at that period state those international, political and economical motives were behind the United States of America in 1898 against Spain Empire. The studies indicate that the reason behind the security disturbance in the area was the Caribbean conflict between Cuba and Spain Empire from 1895 to 1898 and this threatened the political and economical interests of the United States and led the United States to have fears of that the long conflict might give the opportunity to a European force, such as Germany, to have a role in the area since it had economical interests in the Caribbean Sea region. All these factors provoked the United State to have a role in the conflict of the Caribbean Sea region and had a role in the internal revolution against Spain colony in order to get ready to control the area that was considered as a strategic key for its security and to expand its policies in the future. As a result, this paper aims at discussing the motives of the United States of America to content the war of 1898 against Spain Empire and the most important stages of that war. At the same time, it aims at discussing the most important items of the treaty of Paris on the tenth of December in 1898 between the United States of America and Spain.